Absence of a distinctive autoantibody profile in black women with lupus nephritis: comment on the article by McCarty et al (1994)
McCarty and coworkers have pointed out a distinc- tive serologic profile in black women with lupus nephritis (1). We have reviewed the autoantibody profile in 42 of our black patients with systemic lupus erythematosus (SLE), accord- ing to the American College of Rheumatology criteria (2), 21 of whom have lupus nephritis. Our findings are presented herein.